Isolation and Identification of Jellyfish Alkaloid (Bougainvillia Sp) as Immunostimulant to Profile of Protein and Fagosite Activity of Tiger Grouper (Epinephelus Fuscoguttatus) - Andayani, Sri; Fadjar, M.; Rahman, M. Farid (Aquacultura Indonesiana, 2017)
The aim of this research was to know the profil protein and phagocyte activity of tiger grouper (Epinephelus fuscoguttatus). The method used in this research was experimental method with Completely Randomized Design (RAL) consisting of 5 treatment levels ie. K=control group without giving alkaloids and feeding pellets mixed with Jellyfish alkaloid Bougainvillia sp., which were treatment A = 0.5 g, B = 0.75 g, C= 1 g and D = 1.25 g alkaloid/kg of feed conducted in 2 replications. It was challenge tested with Vibrio harveyi of 107 cfu/mL for 5 days. Blood plasma for protein profile and phagocyte activity was performed after giving immunostimulant on day 28 and after being infected on day 34. The results of the study were: (1) alkaloid characteristic was N-1 Benzylalcohol, 4-Octyl Piperidine) and (2) protein profile after immunostimulant addition resulted in 9  bands and sample after infection showed 7 protein bands. The phagocyte activity increases 11.4% to 80.6%. It is suggested to use 1 g of alkaloid/kg of feed as immunostimulant.